“English Language Learners”: An Analysis of Perplexing ESL-Related Terminology - Nina Lee Webster; Chunlei Lu (Language and Literacy: A Canadian Educational e-journal, 2012)
In today’s globalized world it is increasingly important to consciously consider the terminology used when referencing others. The purpose of this paper is to explore and discuss the perplexing array of loosely defined ESL-related terminology in Education. A literature search revealed various terms referring to the same group of learners, the most common being English Language Learner. Through a deconstruction of related terms, an alternative term is proposed: Learner of English as an Additional Language (LEAL). The language learning aspect should not be utilized as a defining characteristic. LEAL is a respectful and culturally appropriate term that utilizes person first language.